Inflammatory response of bioscaffolds decellularized by sonication treatment - Hazwani, Aqilah; Sha'ban, Munirah; Azhim, Azran (Springer, 2018)
Decellularization of sonication system efficiency is dictated by evaluation of host immune response on scaffolds. This aim of this study is to examine the inflammatory response after implantation of bioscaffolds decellularized by sonication treatment at 35 days postsurgery in rats. In this study, aortic tissues decellularized by sonication treatment in 0.1 and 2% of Sodium Dodecyl Sulfate (SDS) detergents. Samples were washed for 5 days in Phosphate Buffer Saline (PBS) following decellularization. Samples were implanted in on the lower right thoracic cavity of rats for 35 days. To examine the inflammatory response, the implanted samples were explanted and evaluated histologically by Hematoxylin Eosin (H-E) staining. From the histological analysis, bioscaffolds decellularized by sonication treatment in response to macrophages shows the minimal inflammatory response. Minimal inflammatory response elicits by bioscaffolds suggests the safety of bioscaffolds prepared by sonication treatment as biomedical implants.